Biological, Physical and Technical Basics of Cell Engineering (Springer Singapore, 2018)
This book presents and discusses recent scientific progress on Cell and Stem Cell Engineering. It predominantly focuses on Biological, Physical and Technical Basics, and features new trends of research reaching far into the 21st century.